Econometric theory - Goldberger, Arthur Stanley (New York: John Wiley, 1964)
This book is intended as a text for a one-year course in econometrics at the graduate level. Its concern is with the methods of estimating and testing relationships among economic variables. Unity of treatment is provided by starting with the classical regression model and proceeding to weaken its several assumptions in turn. The resulting structure should make the book useful also as a reference for those engaged in empirical economic research.
rpm 13/07/2017
Loans
Keywords: Economics, Mathematical; Econometric theory; Economics; Statistics